2021
DOI: 10.1002/tax.12560
|View full text |Cite
|
Sign up to set email alerts
|

Revised phylogenetic position of Nephrocytium Nägeli (Sphaeropleales, Chlorophyceae), with the description of Nephrocytiaceae fam. nov. and Nephrocytium vieirae sp. nov.

Abstract: The common planktonic green algal genus Nephrocytium was traditionally assumed to have a close relationship with the genus Oocystis and accordingly has been included in the family Oocystaceae. Although the position of Nephrocytium within the Oocystaceae has differed according to some authors over the years, its inclusion in the family has not been questioned. Following molecular studies of Oocystis, the Oocystaceae (including Nephrocytium) was removed from the class Chlorophyceae and placed in the Trebouxiophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Oocystaceae are widely distributed, with records and reports all over the world. The early morphological classification assigned the Oocystaceae family to the Chlorophyceae class [8,9], but molecular studies confirmed that this family was a monophyletic group in the Trebouxiophyceae class [10][11][12][13]. Štenclová et al [14] conducted a molecular phylogenetic study on 54 Oocystaceae species in 2017, and divided Oocystaceae into three subfamilies and five clades.…”
Section: Introductionmentioning
confidence: 99%
“…Oocystaceae are widely distributed, with records and reports all over the world. The early morphological classification assigned the Oocystaceae family to the Chlorophyceae class [8,9], but molecular studies confirmed that this family was a monophyletic group in the Trebouxiophyceae class [10][11][12][13]. Štenclová et al [14] conducted a molecular phylogenetic study on 54 Oocystaceae species in 2017, and divided Oocystaceae into three subfamilies and five clades.…”
Section: Introductionmentioning
confidence: 99%